Enthusiastic Students of Poltekkes Semarang Participated in Self-Body Weight Training in the Covid-19 Era: A Survey Study - Dewangga Yudhistira; Haris Kurnianto; Paryadi; Elsa Ariestika; Willy Ikhsan Rizkyanto; Kevin Ramadhan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Abstract: Sports in the era of covid-19 have become a powerful weapon to maintain psychic and physical health for the public. But the question arises, what kind of exercise is good to do in the era of covid-19? Good exercise certainly exercises improves cardiorespiratory and muscle fitness. But sometimes the understanding of physical activity and exercise is still wrong. Physical activity is synonymous with daily activity while exercise is systemized and structured. In addition, regulating the exercise dose including intensity and volume is one of the problems. The purpose of this study is to provide an understanding of the preparation of exercise programs and analyze the enthusiasm of students to take part in self-body weight training. The research method is a survey, the instrument is a questionnaire, and the participants are 34 students of the Semarang Poltekkes male and female genders. The results that student enthusiasm was 60% very high, 38% high, 32% moderate, 21% low, and 1% very low. In conclusion, most students have a high enthusiasm for participating in training, then students state that they understand the content of the material and can compile an exercise program simply by paying attention to the principles of FITT (frequency, intensity, time, and type).